A comprehensive approach to studying motor planning and execution using 3D-printed objects and motion tracking technology - Vyazmin, Alexander; Behera, Sangram; See, Geok Lan; Moiseeva, Victoria; Feurra, Matteo (Frontiers in Human Neuroscience, 2025)
BackgroundMotor planning critically supports efficient hand grasping and object manipulation, involving the precise integration of sensory cues and anticipatory motor commands. Current methods often inadequately separate motor planning from movement execution, thus limiting our understanding of anticipatory motor control mechanisms.ObjectiveThis study aimed to establish and validate a structured methodological approach to investigate motor planning and execution during grasping tasks, using advanced motion tracking technology and standardized 3D-printed geometric objects.MethodsTwenty-one participants performed a grasp-and-place task, requiring manipulation of abstract, non-semantic objects under varying rotation angles (0°, 90°, 180°, 270°). High-resolution kinematic data were captured using an infrared motion tracking system (Smart-DX, BTS Bioengineering, Italy). Novel computational analyses segmented each trial into distinct phases: total movement, movement initiation, reaching, maximal grasp aperture, and object placement. Wrist path length and execution time of each phase were statistically analyzed to assess the influence of object rotation on motor planning and execution.ResultsObject rotation significantly impacted motor planning, as evidenced by prolonged initiation times and altered grasp-related temporal parameters. Specifically, movements involving rotation demonstrated increased movement initiation times, greater grasp apertures, extended placement durations, and longer wrist trajectories compared to non-rotated conditions. Interestingly, symmetrical rotations (180°) facilitated faster and more efficient movements compared to asymmetrical rotations (90°, 270°).ConclusionOur validated methodological framework enables precise isolation and assessment of motor planning processes during grasping movements. This paradigm provides robust tools for fundamental motor control research and has potential clinical applications for evaluating motor planning deficits in patients with neurological impairments.